Pemberdayaan Guru Ngaji melalui Metode Qur’ani Sidogiri untuk Meningkatkan Kemampuan Membaca Teks Arab Al-Qur’an - Azisi, Azisi; Hakimullah, Anil; Badri, Badri (An-Nuqthah, 2025)
Qur'an education in remote areas faces challenges in the form of ancient and less effective learning methods in Quran education in remote areas faces challenges in the form of learning methods that are old-fashioned and less effective in improving the reading ability and fluency of students, especially in traditional communities. Therefore, innovation in teaching methods is needed that are in accordance with the characteristics and needs of students in the area. This study uses the Participatory Action Research (PAR) and Classroom Action Research (CAR) approaches conducted at Madrasah Raudlatul Jannah, Dusun Masegit Bajuran Cerme Bondowoso. The research subjects consisted of 8 students who were selected purposively. The results showed a significant increase in the students' ability to read the Quran, with this finding indicating that the application of the Qur'ani Sidogiri method is effective in improving the ability to read the Quran as well as being a strategy for community empowerment based on Islamic education in remote areas. An innovative, participatory, and adaptive approach can be widely applied to improve the quality of religious education and empower religious teachers in various regions that have similar characteristics.